The Effect of Contribution Income and Claim Expense on Underwriting Surplus/Deficit with Investment Results as a Moderating Variable in Sharia Life Insurance Companies Registered with the OJK for the 2018-2022 Period - Asrori; Sulaeman Jajuli; Budi Sudrajat (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid development of the global economy, supported by massive technological advances, has led to an increase in the potential risks faced by humans in meeting their various life needs. As a result, the challenges in dealing with it are certainly becoming more complex, both in terms of direct and indirect impacts. The purpose of this study is to find out whether or not there is an influence of the various variables studied, Contribution Income (X1), Claim Expense (X2), Underwriting Surplus/Deficit (Y) and Investment Result (Z). This study uses a causal associative method using a quantitative approach. The results of this study show that the variable of contribution income to surplus/underwriting deficit has an effect with a value of sig. 0.021 < 0.05, the variable of claim expense to surplus/underwriting deficit has no effect with a value of sig. 0.105 > 0.05, the variable of investment income to surplus/underwriting deficithas no influence with the GIS value. 0.170 > 0.05, the variable income contribution to investment results has an effect on the value of sig. 0.040 < 0.05, the variable of claim expense on investment results has no effect on the value of sig. 0.703 > 0.05, the variable Income Contribution to Surplus/Underwriting Deficit through investment results as a moderating variable has no effect with a sig. value of 0.151 > 0.05, the variable of claim expense to surplus/Underwriting Deficit through investment results as a moderating variable has no effect with a sig. value of 0.141 > 0.05.